Discrepancy between Admission and Discharge Diagnoses in Central Serbia: Analysis by the Groups of International Classification of Diseases, 10th Revision - Natasa MIHAILOVIC; Dragan VASILJEVIC; Vesna MILICIC; Marina LUKETINA SUNJKA; Snezana RADOVANOVI; Biljana MILICIC; Sanja KOCIC (Tehran University of Medical Sciences, 2020)
Background: Repeated research while using the same methodology can be useful and it can enable relevant conclusions in the same health care system. The aim of our study was to perform comparative analysis of the agreement between admission and discharge diagnostic groups in period 2014-2017 with period 2006-2013 in the Clinical Center of Kragujevac, Serbia. Methods: The 5% simple, random sample was made from the basic set of all hospital reports from Clinical Centre Kragujevac, Serbia, in the period 01.01. 2014 - 31.12. 2017 (n=10228). The first four digits of ICD-10 codes at admission and discharge were compared for agreement. We used discharge diagnosis as a "golden standard". Statistical analysis was performed using Cohen's Kappa statistic. Results: In the period 2014-2017, agreement between diagnosis among the most ICD10 groups increased in comparison with the period 2006-2013. Disagreements between diagnosis in the period 2014-2017 in comparation with period 2006-2013 was associated with increased length of stay in the hospital (7.5 vs. 9.1 days, P<0.01), patients were younger (54 vs 49.6 yr, P<0.01), number of males declined (26.3% vs 16.2%, P<0.05), kappa value decreased in XV ICD10 group and XI ICD10 group and kappa value increased in XIV ICD10 group. Conclusion: Agreement between admission and discharge diagnosis among the most ICD10 diagnostic groups increased. Introduction of a new web application has increased the quality of data, but interpreting it requires the skill of researchers. Further research should identify modifiable causes of discrepancy between admission and discharge diagnoses.